A racionalidade comunicativa em tempos de cibercultura: pela formação de coletivos inteligentes no espaço do saber - Rufino , Emmanoel de Almeida (2017)
This study assumes as object the formative project of intelligent collectives in the contemporary Space of Knowledge, based on the concepts of communicative reason and collective intelligence. In compliance with this referential of rationality, it is based on the Theory of Communicative Action (TCA), following the emancipatory illuminist standard projected in the theory of collective intelligence. It contextualizes the virtual horizons of open learning in the course of the contemporary revolution of computer and telematics systems and the advent of cyberspace in the interim of the XX and XXI centuries AD, as well as the systemic mechanisms that, infiltrated in the interactive networks of this great world cyber life, awaken the formation of intelligent collectives in favor of the promotion of intelligently managed collectives. The objective was to understand the formation of intelligent collectives based on rationally motivated cooperative learning, following the thesis that communicative reason foments cooperative learning processes capable of forming intelligent groups in the Knowledge Space. Inspired by the hermeneutical method, the interpretative view of the object of this study proposes a comprehensive posture of the phenomenon of learning in the universal field – but no totalizable – of cyberspace, privileged locus of the global entanglement of the subjects of the Knowledge Space. In this sense, the construction of the thesis and the steps of his analysis demand the hermeneutical pretension to understand – in the light of the TCA - the guiding principles of reason communicative consistent/propitious to promote the learning cooperatives and collective intelligent, who are at the base of the concept of collective intelligence. Ascertaining the possibility of rationality promoting the development of a culture of cooperative learning and the consequent formation of intelligent collectives in the environments of the Knowledge Space, concludes that the formation of intelligent collectives in cybernetic environments (capable of optimizing the potential of collective intelligence in the Space of Knowledge) passes through the rationalization of communicative in the context of the world of cyberspace life. Appears, therefore, the communicative rationality as a privileged referential to promote intelligent collectives in the Space of Knowledge, especially because its can transform the cyberspacial universe in a world of life emancipated (free of performances noninteractive by subject and systemic instances) and fruitful to the cooperative learning because entangled by competent subjects to speak and act ethically in their interactions, challenging utopia whose “non-place” is a distinct conditioner for our social evolution.